Breast cancer under 40 years of age increasing number and worse prognosis - Dobi Ágnes; Kelemen Gyöngyi; Kaizer László; Weiczner Roland; Thurzó László; Kahán Zsuzsanna (Springer Netherlands, 2011)
Breast cancer at a relatively young age with a poor prognosis is currently exhibiting an increasing incidence. In a retrospective cohort analysis of early breast cancer cases after surgery from our institutional patient registry, 141 patients aged </=40 years constituted the younger group, with 300 randomly selected patients aged >40 years as controls. A significant and steady increase was found in the relative number of younger cases during the years 2004-2009. The histological type and grade and the lymph node status of the cancers differed significantly between the two groups, with more aggressive biological behaviour, a more advanced stage and a worse prognosis in the younger group. Half of the cancers in the younger cohort were ER-negative, while two-thirds in the control group were ER-positive. Comparatively more tumours were PR-positive and HER2-negative in the control group than in the younger group. The rates of triple-negative cases were 25% and 13% in the younger age and the control group, respectively (p = 0.026). Significantly higher mastectomy and axillary block dissection rates were observed in the younger age group, and more chemotherapy was administered than in the control group. Our findings demonstrate the significance of breast cancer in cases aged <40 years, and draw attention to the need for appropriate care in these cases.